2009
DOI: 10.1038/mp.2009.34
|View full text |Cite
|
Sign up to set email alerts
|

High-density SNP association study and copy number variation analysis of the AUTS1 and AUTS5 loci implicate the IMMP2L–DOCK4 gene region in autism susceptibility

Abstract: Autism spectrum disorders are a group of highly heritable neurodevelopmental disorders with a complex genetic etiology. The International Molecular Genetic Study of Autism Consortium previously identified linkage loci on chromosomes 7 and 2, termed AUTS1 and AUTS5, respectively. In this study, we performed a high-density association analysis in AUTS1 and AUTS5, testing more than 3000 single nucleotide polymorphisms (SNPs) in all known genes in each region, as well as SNPs in non-genic highly conserved sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
119
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 61 publications
(91 reference statements)
3
119
1
3
Order By: Relevance
“…38 CNVs encompassing other members of the DOCK (Dedicator of CytoKinesis) family, such as DOCK4 and DOCK8 (located in the 9p24 deletion), have been reported in ASDs. 5,39 However, additional cases of ASD with mutations in this gene need to be identified to confirm that autosomal recessive mutations in DOCK10 can cause ASD.…”
Section: Discussionmentioning
confidence: 99%
“…38 CNVs encompassing other members of the DOCK (Dedicator of CytoKinesis) family, such as DOCK4 and DOCK8 (located in the 9p24 deletion), have been reported in ASDs. 5,39 However, additional cases of ASD with mutations in this gene need to be identified to confirm that autosomal recessive mutations in DOCK10 can cause ASD.…”
Section: Discussionmentioning
confidence: 99%
“…IMMP2L has previously been associated with autism 21,22 and ADHD. 23 Furthermore, in the Decipher database, deletions and duplications spanning IMMP2L are reported in patients with developmental delay and ASD.…”
Section: Discussionmentioning
confidence: 96%
“…24 A recent casecontrol study in families linked to the autism susceptibility locus 1 (AUTS1) detected single-nucleotide polymorphisms (SNPs) and CNV within DOCK4 and IMMP2L, implicating them in autism susceptibility. 20 A DOCK4 deletion segregating in a family with dyslexia, and undetectable in 42500 controls, suggested that DOCK4 may have a role in the aetiology of dyslexia. 25 The GPR85 gene (MIM 605188) is predominantly expressed in the central nervous system, especially in structures exhibiting high levels of plasticity (eg, hippocampal dentate gyrus); it has high evolutionary conservation across three mammalian species, 26 and has been implicated as a potential risk factor for psychiatric disorders.…”
Section: Fish Confirmation Of Partial Deletion Of Immp2lmentioning
confidence: 99%
“…The IMMP2L gene (along with numerous other neurodevelopmental genes) has also recently been implicated in structural variation studies carried out on cohorts of patients with autistic spectrum disorder, 20 and ADHD. 21 Our case does not display any of the classical features of autism, except speech impairment (which is likely to be accounted for by deletion of the FOXP2 gene) or ADHD.…”
Section: Fish Confirmation Of Partial Deletion Of Immp2lmentioning
confidence: 99%